PENGARUH HARGA POKOK PRODUKSI TERHADAP VOLUME PENJUALAN PADA PT. SEMEN BOSOWA MAROS - Vivid Violin (Jurnal Bisnis dan Kewirausahaan, 2019)
Research aims to understand the influence the cost of goods production of the sales volume in pt.Cement bosowa maros maros. districtThis is a quantitative research is analyzing the influence of controlling the prices of basic production of the sales volume in pt.Maros. bosowa cementIn studies there are free of the variable production measured by unit ( rp ) of the total cost and variable terikatnya is measured by unit volume penjulan. tonsThis research is that the whole population data the cost of goods production and the supporting data relating to this research, and included in this study is the report the cost of goods production and the selling data for five in the last is the latest data.Data collection is done using techniques, documentation , interview and observation.Data analysis done by simple, linear regression analysis techniques , correlation and uji-t.